The implementation of knowledge dissemination in the prevention of occupational skin diseases - Wilke, A; Bollmann, U; Cazzaniga, S; Hübner, A; John, S M; Karadzinska-Bislimovska, J; Mijakoski, D; Šimić, D; Simon, D; Sonsmann, F; Stoleski, S; Weinert, P; et al. (Wiley, 2018)
Occupational skin diseases (OSD) have a high medical, social, economic and political impact. Knowledge dissemination from research activities to key stakeholders involved in health care is a prerequisite to make prevention effective.